Arbitration and alternative dispute resolution : how to settle international business disputes (ITC GenevaCH, 2001)
Deals with the different types of disputes that may be encountered in international trade and describes the methods available for preventing or resolving them. Focuses on the fundamental principles applicable to international commercial arbitration. Explains how to draft an arbitration clause and provides selected model clauses.
Bibliography: p.257-260